2015
DOI: 10.3390/ijms160818714
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Chlorotriophenoxy Radicals from Complete Series Reactions of Chlorotriophenols with H and OH Radicals

Abstract: The chlorothiophenoxy radicals (CTPRs) are key intermediate species in the formation of polychlorinated dibenzothiophenes/thianthrenes (PCDT/TAs). In this work, the formation of CTPRs from the complete series reactions of 19 chlorothiophenol (CTP) congeners with H and OH radicals were investigated theoretically by using the density functional theory (DFT) method. The profiles of the potential energy surface were constructed at the MPWB1K/6-311+G(3df,2p)//MPWB1K/6-31+G(d,p) level. The rate constants were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 49 publications
(65 reference statements)
2
15
0
Order By: Relevance
“…The reliability and accuracy of the MPWB1K/6-311+G(3df,2p)// MPWB1K/6-31+G(d,p) level for the geometries, frequencies and energy calculation in this study have been confirmed in our previous works on PCTA/DT formation with 2,4-DCTP as the precursor [29,39]. The data was compared with data from Yu and Pan calculated at the BB1K/6-311+G(3df,2p)//BB1K/6-311G(d,p) level [30,36].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The reliability and accuracy of the MPWB1K/6-311+G(3df,2p)// MPWB1K/6-31+G(d,p) level for the geometries, frequencies and energy calculation in this study have been confirmed in our previous works on PCTA/DT formation with 2,4-DCTP as the precursor [29,39]. The data was compared with data from Yu and Pan calculated at the BB1K/6-311+G(3df,2p)//BB1K/6-311G(d,p) level [30,36].…”
Section: Resultssupporting
confidence: 82%
“…The calculated potential barriers (Δ E ) and the reaction heats (Δ H ) at the MPWB1K/6-311+G(3df,2p)//MPWB1K/6-31+G(d,p) level involved in the formation of R1, R2 and DR radicals from 2,4-DCTP abstracted by the OH, H and Cl are given in the Figure 1a–c. In Figure 1, data of 2,4-DCTP thiophenoxyl-H abstraction by OH and H were cited from our previous studies [39]. All the optimized transition state geometries for 2,4-DCTP abstracted by OH, H and Cl radicals are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential barriers (Δ E ) and the reaction heats (Δ H ) of 2,4-DCTP and 2,4,6-TCTP thiophenoxyl-hydrogen cleavage and abstraction by H, OH, O( 3 P), and Cl were calculated at the MPWB1K/6-311+G(3df,2p) level in Table 1 . Data of 2,4-DCTP and 2,4,6-TCTP thiophenoxyl-hydrogen cleavage and abstraction by H and OH were cited from our previous studies [ 39 ]. All the abstraction steps are strongly exothermic.…”
Section: Resultsmentioning
confidence: 99%
“…The potential barriers (Δ E ) and the reaction heat (Δ H ) which are calculated at the MPWB1K/6-311+G(3df,2p)//MPWB1K/6-31+G(d,p) level for the formation of C(T)PR1, C(T)PR2, C(T)PDR, (T)PR2, and (T)PDR from 2-C(T)P abstracted by the H and OH are given in the Figure 1a,b. In Figure 1, data of sulfydryl/hydroxyl-H abstraction of 2-C(T)P by H and OH are cited from our previous studies at the MPWB1K/6-311+G(3df,2p)//MPWB1K/6-31+G(d,p) level [44,45,46]. Pan et al and Yu et al also studied the formation of C(T)PR1, C(T)PR2, C(T)PDR, (T)PR2, and (T)PDR from 2-C(T)P molecules abstracted by H radical at the BB1K/6-311+G(3df,2p)//BB1K/6-311G(d,p) level [27,41].…”
Section: Resultsmentioning
confidence: 99%